Microclima em sistemas de integração e características quanti-qualitativas da sombra de espécies arbóreas nativas e cultivada, no cerrado - Karvatte Junior, Nivaldo (2014)
Were avaluated the microclimate in integrate systems, with determination of thermal comfort indices to sun and shade, and the quantitative and qualitative characteristics of shade trees, native and cultivated in Cerrado species. The experiment was conducted at Embrapa Beef Cattle, Campo Grande , in the period July-September 2013, in an area with three integrate systems (iCLF-1 , with 357 eucalyptus trees/ha; iCLF-2, with 227 eucalyptus trees/ha and ILP with 5 native trees/ha ), with Brachiaria brizantha cv. BRS Piatã. The microclimate has been reported in the months of July, August and September, registering for that, data of air temperature (Ta), the wet bulb temperature (WBT), black globe temperature (BGT), relative humidity (RH) and wind speed (WS), the sun and shade, from 08:00 a.m. to 05:00 p.m. in the three systems. Subsequently, the rates of temperature and humidity (THI) and globe temperature and humidity (BGHI), and radiant thermal load (RTL) were calculated. The settings of the shadows cambará, cumbaru and eucalyptus were determined according to Silva (2006), in July, August and September, at 09:00 a.m., 12:00 and 03:00 p.m., from the total height (HT), stem height (HS), length canopy (LC) and crown diameter (CD). Integrate systems crop-livestock-forest are effective in improving the microclimate of the production environment, and the amount of drop shadow is different depending on the tree species and its configuration canopy